Surface characterization and adsorptive performance of manganese cobaltite (MnCo2O4) for dye removal: experimental and statistical insights - Guven, Meltem; Azkeskin, Selen Avci; Ugraskan, Volkan; Isik, Birol (ELSEVIER, 2026)
This study examines the surface characteristics of MnCo2O4 produced using the co-precipitation process and assesses its efficacy in adsorbing Congo red (CR) from aqueous solutions. The surface properties were thoroughly analyzed using inverse gas chromatography (IGC), FTIR-ATR, SEM, XRD, zeta potential, BET, and pHpzc assessments, indicating an acidic surface structure (KD/KA = 0.8427) with an average pore diameter of 4.887 nm, a specific surface area of 10.409 m2/g, and a positive surface charge below pHpzc (6.46), facilitating the adsorption of anionic dyes. Adsorption conditions were optimized via a Taguchi L25 orthogonal array, with the best parameters identified as an initial dye concentration of 100 mg/L, pH 4, a contact period of 30 min, and an adsorbent dosage of 0.1 g. A maximum removal efficiency of roughly 99.81% was attained under these settings. Equilibrium investigations demonstrated that adsorption adhered to the Langmuir isotherm model, with a maximum adsorption capacity (qm) of 44.17 mg/g at 298 K, signifying monolayer adsorption. A kinetic study demonstrated that the adsorption process adhered to the pseudo-first order model, suggesting a predominantly physical adsorption mechanism. Thermodynamic characteristics indicated that the adsorption process was spontaneous (Delta G degrees = -29.51 to -34.29 kJ/mol), endothermic (Delta H degrees = 17.96 kJ/mol), and driven by entropy, with enhanced performance at elevated temperatures. Adsorption was primarily influenced by electrostatic attraction between the positively charged MnCo2O4 surface and anionic CR molecules, supplemented by Van der Waals interactions and weak coordination bonds. Moreover, actual wastewater trials showed significant removal efficiency (up to 97.9%), underscoring the practical utility of MnCo2O4 as an efficient adsorbent for the remediation of dye-contaminated water.
Keywords: Adsorption; ANOVA tests; Congo red; Inverse gas chromatography; Manganese cobaltite; Surface properties; Taguchi optimization; CONGO RED-DYE; ACTIVATED CARBON; NANOPARTICLES; DEGRADATION; TEMPERATURE; KINETICS; GLASS; Chemistry